PENDIDIK SEBAGAI MODEL DALAM MEWUJUDKAN PESERTA DIDIK YANG BERKARAKTER - amin efendi (Tarbawiyah Jurnal Ilmiah Pendidikan, 2018)
Teachers are an important role in the world of education, they have responsibility to develop the potential of learners in terms of spiritual, intellectual, moral, and life skills so that they could achieve educational goals. This goal will be achieved if all elements of education can be fulfilled and carried out properly, such as: goals, learners, educators, methods, curriculum, environment, and educational facilities. Teachers must have sufficient competence to support their profession, including; pedagogical, personal, professional, and social competence. In carrying out the educational process educators should be able to be role models for their students, and could be ideal teacher, placing itself as a model or a model that deserves to digugu and imitated by learners both in personality traits, attitudes, words and deeds. With it hoped the teacher could able to instill character values ​​to learners, include: religious values, honesty, tolerance, discipline, hard work, creative, independent, democratic, curiosity, nationalism, love of country, respect for the achievements, communicative, love peace, love to read, care about the environment, social care, and responsibility. Through exemplary demonstrated by educators is expected to manifest learners who have character and intelligent as intellectually, emotionally and spiritually.